FACTORS ASSOCIATED POST-PARTUM CONTRACEPTION PLANNING - Zulfa, Sheila Nurhaliza; Ayudha, Mita Dwi; Ernawaty, Ernawaty; Kurniawan, Afif (Universitas Airlangga, 2024)
The problem of stunting that occurs in Indonesia is caused by one of the sensitive factors, namely bad parenting. Improper parenting can occur in mothers whose children are born too close together (<2 years). Postpartum contraception can also be a solution for those who are